Karakteristik Modul Endoprima Lemah - Ainurrofiqoh, Dewi Ika (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
In this research, we studied weakly endoprime module, which is a development of weakly prime module by reviewing its fully invariant submodule. This is similar to the development of endoprime module from prime module. This primary objective of this research are to determine the relationship between weakly endoprime module and endoprime module and examine the fully invariant submodules of weakly endoprime module. The method employed in this research involves studying the relationship between weakly prime modules and prime modules, endoprime modules and prime modules, as well as weakly endoprime modules and weakly prime modules. The results obtained are that each endoprime module is a weakly endoprime module, but the converse is not necessarily true. Moreover, a fully invariant submodule of a weakly endoprime module is not necessarily a weakly endoprime module.